Utilization of Pottery as Well as Shaping Art and Community Creativity Through Clay in Anyer Area, Serang Regency - Nawawi, Muhammad; Maharani, Nurul Liza; Amelia, Farisa; Habibah, Soraya; Pratama, Muhammad Arief; Nurlela, Fella; Zamsani, Rizqiana (EQUATOR SINAR AKADEMIA, 2024)
Anyer is located on the west coast, Serang Regency, Banten. Anyer is famous for beach tourism. But apart from the famous Anyer Beach, the pottery village provides an extraordinary tourist experience. The grain making center in Anyer is precisely located in Bandulu Village. So the pottery from this area is called bandulu pottery. Bandulu pottery is very famous because it is marketed quite widely outside the Anyer tourist area. This Bandulu pottery prioritizes training its visitors rather than selling its products. Usually their target market is students from elementary to high school, university students and other general visitors.